Factors influencing midwives in providing Hepatitis B immunization for newborns in the Bitefa health center working area - Nastiti, Deasy Harini (Paspama Institute, 2024)
The prevalence of Hepatitis B in Indonesia is due to delays in immunization. The risk of chronic hepatitis B is much greater when infection occurs early in life compared to infection that occurs in adulthood. The purpose of the study was to determine the factors that influence midwives in providing Hepatitis B immunization to newborns in the Bitefa Health Center Working Area. This type of research is a survey with a cross sectional method. The study population was all mothers who gave birth in the working area of the Bitefa Health Center assisted by midwives as many as 102 people, and the entire population was used as a research sample. Data analysis used was univariate, bivariate with Chi Square test, and multivariate with multiple logistic regression test. The results showed the provision of hepatitis B immunization in newborns by midwives as many as 37 people (36.3%), while those who did not provide hepatitis B were 65 people (63.7%). The results showed that motivation (p=0.036), midwife ability (p=0.031) and midwife perception (p=0.031) influenced the provision of Hepatitis B immunization. From the results of multivariate analysis obtained the variable that has the greatest influence is the ability of midwives with an Exp B value = 2.899. Research conclusion is the low immunization coverage is due to the lack of information obtained by mothers from health workers, especially midwives regarding hepatitis B immunization. Suggestions need to improve health services, especially antenatal care checks and provide information to mothers about the importance of complete basic immunization, especially hepatitis immunization.